2018
DOI: 10.2478/pepsi-2018-0003
|View full text |Cite
|
Sign up to set email alerts
|

Personality, Job Resources, and Self-Efficacy as Predictors of Volunteer Engagement in Non-Governmental Organizations

Abstract: As volunteer engagement in non-governmental organizations vary between individuals, it is vital to get to know its predictors. It can be of profit to volunteers and the ones who profit from their activities. The aim of present study was to examine a model explaining volunteer engagement examining volunteer self-efficacy as a mediator and personality traits, job resources (skill variety and autonomy) as its predictors. Respondents (N = 165) were asked to fill in questionnaires accessible online. Those consisted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 40 publications
1
11
0
5
Order By: Relevance
“…Penelitian mengenai kepribadian dengan work engagement pada relawan pernah dilakukan oleh Kossowska & Laguna (2018). Temuan dalam penelitian ini terdapat perbedaan dengan temuan pada penelitian Kossowska & Laguna (2018). Didalam penelitian ini dimensi yang berpengaruh terhadap work engagement relawan yaitu agreeableness, sementara dimensi yang lain tidak berpengaruh.…”
Section: Uji Multikolinieritasunclassified
See 3 more Smart Citations
“…Penelitian mengenai kepribadian dengan work engagement pada relawan pernah dilakukan oleh Kossowska & Laguna (2018). Temuan dalam penelitian ini terdapat perbedaan dengan temuan pada penelitian Kossowska & Laguna (2018). Didalam penelitian ini dimensi yang berpengaruh terhadap work engagement relawan yaitu agreeableness, sementara dimensi yang lain tidak berpengaruh.…”
Section: Uji Multikolinieritasunclassified
“…Didalam penelitian ini dimensi yang berpengaruh terhadap work engagement relawan yaitu agreeableness, sementara dimensi yang lain tidak berpengaruh. Sedangkan pada penelitian Kossowska & Laguna (2018) menunjukkan dimensi yang berpengaruh yaitu conscientiousness, sementara dimensi lainnya tidak berpengaruh.…”
Section: Uji Multikolinieritasunclassified
See 2 more Smart Citations
“…Similarly [21] describes entrepreneurs and employees are often more engaged, moti-Open Journal of Business and Management vated and, consequently, successful in their tasks due to the high levels of selfefficacy and sufficient amount of resources in the organization. Kossowska & Laguna [22] found that the result of hierarchical regression analyses have shown conscientiousness, skill variety and self-efficacy are statistically significant predictors of volunteer non-profit organization of Poland.…”
Section: Introductionmentioning
confidence: 99%